Preparation and In vitro Investigation of Chitosan Compressed Tablets for Colon Targeting - Negar Bashardoust; Josephine Leno Jenita; Parvin Zakeri-Milani (Tabriz University of Medical Sciences, 2011)
Purpose: The aim of the present study was minimizing the drug release in upper gastro intestinal tract and targeting to colon by using the principles of compression coat. Methods: Compression coated tablets of Ibuprofen were prepared by direct compression method using chitosan (300, 250, 200 & 175 mg). Tablets were evaluated for their physicochemical properties and in vitro drug release studies. In vitro drug release studies were performed with and without rat caecal contents. Results: In the rat caecal contents tablets showed enhanced drug release due to degradation of chitosan coat by colonic colonic enzymes. The in vitro release studies in pH-6.8 phosphate buffer containing 2% w/v of rat caecal contents showed the cumulative percentage release of Ibuprofen after 26h as 31.94% ±0.59, 67.89% ± 0.45 and 55.87 % ± 0.45 and 82.52 % ± 0.92 respectively. Coatthickness and amount of chitosan controls the release rate. Formulations are best fitted with Korsmeyer-Peppas kinetics and mechanism of drug release was non-Fickian. FTIR studies reveals there is no drug-polysaccharide interaction. F1 formulation was a promising system for drug targeting to colon. Conclusion: Based on the obtained results chitosan as a press coat could target ibuprofen to the colon.